The Value of Compulsory Military Service in the Soviet Army (1967–1990) from the Conscripts’ Perspective - Šimanauskaitė, Ieva (Lietuvos istorijos studijos, 2024)
This article presents a study using qualitative research methods, including oral history and content analysis, to explore the value of compulsory military service in the Soviet Army (1967–1990). The investigation considers both the ideological context and the perspectives of the individuals who were serving. Periodicals such as Komjaunimo tiesa and Jaunimo gretos, published in the Lithuanian Soviet Socialist Republic (LSSR) between 1967 and 1990, focus on the soldier’s identity. However, these publications often present a superficial view, emphasizing qualities such as ‘fearlessness’, ‘toughening’, ‘physical strength’, and ‘masculinity’. In contrast, interviews with Lithuanian conscripts reveal a wide range of experiences and perspectives on the military service, shaped by their social environment, personal experiences, and education. While many view their military service as ‘lost years’, some men recognize positive outcomes, such as increased maturity and greater independence. The harsh conditions and difficult living environment during their service also led to feelings of alienation and caution, reinforcing certain Soviet lifestyle habits, such as dishonesty, theft, adaptation, and time-wasting. Although the length of service typically ranged from 2 to 3 years, for some men, it remains a significant life adventure or a troubling memory, often revisited through humorous stories or a desire to connect with others who share similar experiences.